Surface-Floating Pupal Exuviae of Chironomidae (Diptera) in Urban Streams: is There a Best Time of Day to Sample Them? - Santana, Herick Soares; Lima, Vanessa Araújo; Simião-Ferreira, Juliana (EntomoBrasilis, 2016)
Abstract. The use of pupal exuviae is a method that allows evaluating the environmental condition using information provided by the diversity of Chironomidae. The exuviae can disperse over distances up to 100 m from where the adults emerged, allowing perform detailed studies on the local community. The aim of this study was verify whether there are differences in the taxonomic richness and abundance in the emergence of pupal exuviae of Chironomidae during different periods of day in three urban Cerrado streams. The samples were taken in the dry season of July 2011, in three first-order streams located nearby Anápolis municipality, Goiás State, Brazil, using drift nets for a period ranging from 8 to 20 h, with removal and replacement of the drift nets every two hours period. 6.129 exuviae were collected in the three streams and the Onconeura and Polypedilum generatotaled 70% of all individuals collected. The time at 16 h was the most representative of the number of exuviae collected, while the first time (8 h) had the lowest amount of exuviae. The genera richness and abundance of exuviae did not show changes according to the time of day on the streams, indicating that there is not a period in which there is a greater frequency of adult emergence of Chironomidae. Exúvias de Pupa de Chironomidae (Diptera) em Riachos Urbanos de Cerrado: existe um Melhor Horário do Dia para Amostrar? Resumo. O uso de exúvias de pupa é um método que permite avaliar condições ambientais utilizando informações da diversidade de Chironomidae. Exúvias de pupas podem se dispersar em distâncias de até 100 m dos locais onde os adultos emergiram, permitindo realizar estudos sobre a comunidade local. O objetivo deste estudo foi verificar se existem diferenças na riqueza taxonômica e abundância em exúvias surgidas de pupa de Chironomidae durante diferentes períodos do dia em córregos urbanos do Bioma Cerrado. As amostras foram coletadas na estação seca de julho de 2011, em três riachos de primeira ordem localizados próximos à cidade de Anápolis, Goiás, Brasil, utilizando redes de deriva por um período que variou de 8-20 h, com remoção e substituição das redes a cada duas horas. Foram coletadas 6129 exúvias nos três córregos e os gêneros Onconeura e Polypedilum totalizaram 70% de todos os indivíduos coletados. O horário de 16 h foi o mais representativo em relação ao número de exuvias coletadas, enquanto que as exúvias coletadas às 8 h foram menos abundantes. A riqueza e a abundância de gêneros de exúvias não apresentaram mudanças de acordo com o horário do dia nos córregos estudados, indicando que não existe um período no qual há uma maior frequência de aparecimento de Chironomidae adulto.